Weather Elements and Frost Occurrence in Arid Zone of Haryana - Satyawan, Satyawan; Niwas, Ram; Khichar, M L (Annals of Arid Zone, 2016)
The study was conducted at CCS Haryana Agricultural University Hisar.The daily meteorological data of winter seasons (December to February) of past20 years from 1982 to 2002 were used. Mean frosty days were maximum in January(12.7) followed by December (8.5) and February (5.7). The CV was less in Januaryas compared to December and February. Maximum probability of frost occurrencewas 0.70 on 24th January. Grass minimum temperature was correlated with weatherparameters of two preceding days. Grass minimum temperature was significantlycorrelated with minimum temperature; morning and. evening actual vapor pressureand morning and evening relative humidity. Minimum temperature and morningactual vapor pressure of previous day (logarithmic relationship) individually explainedthe variability in grass minimum temperature of next day up to 76%.Key words: Frost, grass minimum temperature.